Analysis of a Mathematical Book-Writing Training Program: A Case Study of Formulas and Smart Tricks for Mathematics Education Students - Maswar Maswar; Moh. Atikurrahman (LP2M Universitas Ibrahimy, 2026)
A textbook is a set of learning materials that are systematically arranged and display the integrity of the competencies that will be mastered by students in learning activities. This Community Service (CS) activity aims to provide training in Writing 1001 Types of Formulas and Smart Tricks for Elementary and Middle School Mathematics to students who are actively studying and come from several classes of the Mathematics Education study program, Ibrahimy University, Situbondo. The understanding gained from this training can later be used to produce writings in the form of elementary and middle school mathematics books. A total of twenty-six students participated in this writing training, which was held twice a week for one month, namely in February 2025. From the results of the pre-test and post-test, it was seen that each participant experienced an increase in writing scores after receiving the training. In addition, data from the interview process showed the perceptions of the participants who gave a positive response to this book-writing training. This CS activity implies that we know what difficulties Mathematics Education students experience in learning to write books and solutions, and what can be done to help them. However, the drawback of this book-writing training is that it only involved a relatively small number of participants and in a relatively short time. The next writing training can recruit more participants and increase the training time longer, so that maximum results can be obtained.